Oligonucleotide Microarrays Identified Potential Regulatory Genes Related to Early Outward Arterial Remodeling Induced by Tissue Plasminogen Activator - Plekhanova, Olga; Parfyonova, Yelena; Beloglazova, Irina; Berk, Bradford C.; Tkachuk, Vsevolod (Frontiers in Physiology, 2019)
Constrictive vascular remodeling limiting blood flow, as well as compensatory outward remodeling, has been observed in many cardiovascular diseases; however, the underlying mechanisms regulating the remodeling response of the vessels remain unclear. Plasminogen activators (PA) are involved in many of the processes of vascular remodeling. We have shown previously that increased levels of tissue-type PA (tPA) contributes to outward vascular remodeling. To elucidate the mechanisms involved in the induction of outward remodeling we characterized changes in the expression profiles of 8799 genes in injured rat carotid arteries one and four days after recombinant tPA treatment compared to vehicle. Periadventitial tPA significantly increased lumen size and vessel area, encompassed by the external elastic lamina, at both one and four days after treatment. Among 41 differentially expressed known genes one day after tPA application, 5 genes were involved in gene transcription, 5 genes were related to the regulation of vascular tone (for example, thromboxane A2 receptor (D32080) or nonselective-type endothelin receptor (S65355)), and 8 genes were identified as participating in vascular innervation (for example, calpain (D14478) or neural cell adhesion molecule L1 (X59149)). Four days after injury in tPA-treated arteries, 4 genes, regulating vascular tone, were differentially expressed. Thus, tPA promotes outward arterial remodeling after injury, at least in part, by regulating expression of genes in the vessel wall related to function of the nervous system and vascular tone.